Deskripsi Kemampuan Berpikir Kreatif Matematis Ditinjau dari Tingkatan Habits of Mind - Asriningsih, Tafsillatul Mufida (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2022)
Abstract The purpose of the study was to describe students' mathematical creative thinking abilities based on different levels of Habits of Mind (HoM). This research was a qualitative descriptive study. The research subjects consisted of one student with a moderate level of HoM and one student with a low level of HoM. Both subjects were in VII grade of junior high school. Data collection was carried out using the HoM questionnaire technique, open ended tests on geometry, and interviews. The results showed that the highest criteria of creative thinking that met by students with moderate levels of HoM were fluency and flexibility, but did not meet the novelty criteria. While students with low levels of HoM do not meet all the criteria of creative thinking. Keywords: creative thinking ability, habits of mind, open ended, geometry